Patterns of inclusive growth in developing Asia: Insights from an enhanced growth-poverty elasticity analysis - Cielito F. Habito (Asian Development Bank Institute (ADBI), 2009)
The primary objective of this research is to identify key factors that explain the observed wide variation in patterns of inclusiveness of economic growth - defined here as gross domestic product (GDP) growth that leads to significant poverty reduction - in Asia. In exploring this relationship, this study goes beyond defining poverty by the income or expenditure yardstick alone, but examines a more holistic measure of poverty that considers its multidimensional nature. Factors that influence the degree of poverty reduction that accompanies economic growth (herein referred to as the poverty elasticity of growth or PEG) include the sectoral composition of the economy and its growth; the nature, size, and pattern of public investments (particularly on social services and agriculture); and quality of governance. As construction of a consistent panel data set was beyond the time constraints for the study, PEG is calculated for Asian countries as an arc elasticity over the 1990-1996 and 2000-2006 periods, and analyzed against available measures of the above-named factors from statistics compiled by the Asian Development Bank (ADB), World Bank, and the United Nations Development Programme (UNDP). Pairwise analyses using scatterplots, simple regressions, and multiple regressions were employed to determine systematic relationships between the PEG and its likely determinants. Results affirmed the significant impact of quality of governance, public expenditures on social services, and contribution of agriculture to GDP growth, in that order of importance. There is likewise evidence that manufacturing growth has had a bearing on the inclusiveness of growth, especially in Southeast Asia in recent years. Results of the analysis also showed how dramatic differences in characterization of countries can result when a multidimensional poverty measure is employed rather than a unidimensional one based only on income or expenditure. This points to the need for a more holistic view and assessment of poverty when using it as a guide for various development interventions.
Keywords: O11; O15; O20; O53; 330